The APOE–Microglia Axis in Alzheimer’s Disease: Functional Divergence and Therapeutic Perspectives—A Narrative Review - Aiwei Liu; Tingxu Wang; Liu Yang; Yu Zhou (Brain Sciences, 2025)
Apolipoprotein E (APOE) alleles play distinct roles in the pathogenesis of Alzheimer’s disease (AD), with APOEε4 being the strongest genetic risk factor for late-onset AD, while APOEε2 appears protective. Despite extensive research, the precise mechanisms by which APOE alleles contribute to AD pathology remain incompletely understood. Recent advances in multi-omics technologies and single-cell analyses have revealed that APOE alleles shape microglial phenotypes, thereby affecting amyloid clearance, inflammatory responses, tau pathology, and lipid metabolism. In this review, we provide a detailed overview of how APOE alleles differentially regulate microglial activation, inflammatory signaling, phagocytic activity, and lipid metabolism in the context of AD, with a particular focus on the APOEε4-mediated disruption of microglial homeostasis via pathways such as TREM2 signaling, NF-κB/NLRP3 activation, ACSL1 upregulation, and HIF-1α induction. These insights not only advance our understanding of APOE allele-specific contributions to AD pathology, but also highlight novel therapeutic strategies targeting the APOE–microglia axis.